(untitled) (Revista de Ciências Agroveterinárias, 2025)
The objective of this study was to evaluate the combination of nitrogen (N), phosphorus (P), and potassium (K) doses associated with the maximum total dry matter production of Italian ryegrass (Lolium multiflorum Lam). The experiment was conducted in pots in a greenhouse at the Federal University of Pampa, Campus Itaqui – RS, Brazil. A total of 20 treatments were tested, resulting from the combination of four N doses (0, 75, 125, and 175% of the recommended N rate) and five doses of P and K (0, 50, 100, 150, and 200% of the recommended rates). The experimental design was completely randomized in a 4 x 5 factorial arrangement with four replicates. Two, five, six, and five cuts were made referring to doses of N, 0, 75, 125, and 175%, respectively, as the plant reached 20 cm in height to obtain total dry matter (DM) production. Data were subjected to analysis of variance (P < 0.05) using the F test with adjusted regressions. The model with the highest significance level between linear and quadratic regressions was selected. Dry matter production (kg ha-1) exhibited a quadratic response to increasing N doses across all P and K levels, with higher production between levels 75 and 125% of N. The highest yield was obtained with 125% of the recommended N dose combined with 150% of the recommended P and K doses, with a mean DM production of 625 kg ha-1.